Peran Supervisi Kepala Madrasah dalam Meningkatkan Profesionalisme Guru di Mi Al-Kalam Denpasar Tahun Pelajaran 2019/2020 - Zahrotil, Diana; Mahrusun, Mahrusun; Hidayat, Tauhid (Faidatuna, 2022)
This research is motivated by the phenomenon that the role of headmaster supervision in improving the professionalism of teachers at MI Al Kalam Denpasar is not as expected that the head of the madrasah supervises there are still some teachers who teach not their scientific discipline, teachers who are concurrently madrasah leaders, service teachers who do not have a S1 diploma. This is very important in paying attention to professional competence for a teacher. The purpose of this study was to determine the role of headmaster supervision in improving the professionalism of teachers at MI Al Kalam Denpasar and to determine the inhibiting and supporting factors in improving teacher professionalism at MI Al Kalam Denpasar. This type of research is descriptive with a qualitative approach with three data collection techniques, namely: observation, documentation, and interviews. The results of this study are the role of supervision of madrasah principals to improve teacher professionalism at MI Al Kalam, namely leading teachers and other education personnel, to improve teaching including stimulating, selecting teachers' positions, selecting, and revising educational goals, teaching materials and teaching methods and teaching evaluation.